A Flexible 3D Multifunctional MgO‐Decorated Carbon Foam@CNTs Hybrid as Self‐Supported Cathode for High‐Performance Lithium‐Sulfur Batteries. (11th August 2017) - Xiang, Mingwu; Wu, Hao; Liu, Heng; Huang, Ju; Zheng, Yifeng; Yang, Li; Jing, Peng; Zhang, Yun; Dou, Shixue; Liu, Huakun
Abstract : One of the critical challenges to develop advanced lithium‐sulfur (Li‐S) batteries lies in exploring a high efficient stable sulfur cathode with robust conductive framework and high sulfur loading. Herein, a 3D flexible multifunctional hybrid is rationally constructed consisting of nitrogen‐doped carbon foam@CNTs decorated with ultrafine MgO nanoparticles for the use as advanced current collector. The dense carbon nanotubes uniformly wrapped on the carbon foam skeletons enhance the flexibility and build an interconnected conductive network for rapid ionic/electronic transport. In particular, a synergistic action of MgO nanoparticles and in situ N‐doping significantly suppresses the shuttling effect via enhanced chemisorption of lithium polysulfides. Owing to these merits, the as‐built electrode with an ultrahigh sulfur loading of 14.4 mg cm −2 manifests a high initial areal capacity of 10.4 mAh cm −2, still retains 8.8 mAh cm −2 (612 mAh g −1 in gravimetric capacity) over 50 cycles. The best cycling performance is achieved upon 800 cycles with an extremely low decay rate of 0.06% at 2 C. Furthermore, a flexible soft‐packaged Li‐S battery is readily assembled, which highlights stable electrochemical characteristics under bending and even folding. This cathode structural design may open up a potential avenue for practical application of high‐sulfur‐loading Li‐S batteries toward flexible energy‐storage devices. Abstract : A 3D, flexible, multifunctional hybrid comprised of nitrogen‐doped carbon foam@carbon nanotubes decorated with ultrafine MgO nanoparticles (CF@CNTs/MgO) is designed by a structural engineering strategy. This hybrid is used as the self‐supported current collector for high‐performance Li‐S batteries with high sulfur‐loading.